2011
DOI: 10.1111/j.1442-9071.2010.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic approaches in the treatment of diabetic keratopathy: a review

Abstract: The cornea is densely innervated, and the integrity of these nerve fibres is critical in maintaining the refractive and protective functions of the cornea. Many ocular and systemic diseases can adversely affect corneal sensory nerves and consequently impair their function, with vision loss being the inevitable consequence of severe corneal neurotrophic ulceration. However, current standard treatments regimens are often ineffective. Over the past three decades, the role of growth factors in maintaining the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 101 publications
0
80
0
4
Order By: Relevance
“…43 This condition is difficult to manage clinically, requires multimodal treatment approaches, may fail to respond to conventional treatment, and eventually leads to visual impairment. 44,45 By monitoring corneal nerve alterations in vivo, application of IVCM may also demonstrate efficacy of topically applied neuropeptides and neurotrophins in clinical studies to treat neurotrophic keratitis and DK.…”
Section: Discussionmentioning
confidence: 99%
“…43 This condition is difficult to manage clinically, requires multimodal treatment approaches, may fail to respond to conventional treatment, and eventually leads to visual impairment. 44,45 By monitoring corneal nerve alterations in vivo, application of IVCM may also demonstrate efficacy of topically applied neuropeptides and neurotrophins in clinical studies to treat neurotrophic keratitis and DK.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, SP, secreted by corneal sensory nerve fibers, may be the key neurotransmitter and neuropeptide that mediates corneal nociception transmission and provides trophism to the corneal epithelium. Furthermore, as for the treatment of diabetic keratopathy, many growth factors, cytokines, and various agents have been evaluated for their capacity to accelerate corneal wound healing (40). However, SP and its functional derivative (FGLM-amide), with the advantages of smaller molecules and higher efficiency, have been shown to be effective for the treatment of persistent corneal epithelial defects in clinical studies (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as for the treatment of diabetic keratopathy, many growth factors, cytokines, and various agents have been evaluated for their capacity to accelerate corneal wound healing (40). However, SP and its functional derivative (FGLM-amide), with the advantages of smaller molecules and higher efficiency, have been shown to be effective for the treatment of persistent corneal epithelial defects in clinical studies (40)(41)(42). In addition, we found that SP promoted the regeneration of nerve fibers in diabetic corneal epithelium and accelerated trigeminal neuronal growth in vitro that was impaired by high glucose (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes adversely affects corneal sensory nerves and consequently impairs their function, with vision loss being the inevitable consequence of severe corneal neurotrophic ulceration. However, current standard treatment regimens are often ineffective (3).…”
Section: Introductionmentioning
confidence: 99%